Medieval Latin palaeography : a bibliographical introduction - Boyle, Leonard E. (Toronto medieval bibliographies, 1984)
The aim of this bibliography is to present students with as wide a survey as possible of all the aspects they must consider, and all the tools they must employ, in order to evaluate the communication in any book, document, or inscription from the Middle Ages on which they would be working. From the Author's Preface.